Characterization of mechanical and thermal properties of esterified lignin modified polypropylene composites filled with chitosan fibers - Tanjung, Faisal A.; Kuswardani, Retna A.; Idumah, Christopher I; Siregar, Januar Parlaungan; Abdul Karim, . (SAGE Publications Ltd, 2022)
A comparative study was performed on the use of esterified alkaline lignin (AAL) and esterified organosolv lignin (AOSL) as the interfacial modifying agent to improve the properties of polypropylene-chitosan composites. Chitosan was chemically modified through a reaction with the esterified lignin in an alcohol medium. The composites were prepared using an internal mixer and hot-pressed method. Both modified chitosan showed a different chemical structure upon modification with the esterified lignins as confirmed by Fourier transform infrared spectroscopy spectra. With a lower molecular weight, the AOSL attachment on the chitosan surface resulted in more efficiency in decreasing hydrophilic characters. Tensile tests showed the increased tensile strength by 32.15% and 26.43% for AOSL-modified composites and AAL-modified composites as compared with the unmodified composites. Overall, the AOSL was superior in improving the mechanical strength and thermal stability of the composites, while the AAL exhibited the most apparent enhancement in ductility and crystallization.